CREATIVITY OF VIKTOR EFIMENKO IN THE CONTEXT OF THE DEVELOPMENT OF UKRAINIAN BOOK GRAPHICS (the last third of the twentieth century) - Спасскова, О. П. (Art and Design, 2019)
The purpose of the work is to study the creativity of the Odessa graphic artist Viktor Efimenko (1933-1994) in the context of the development of Ukrainian book graphics of the last third of the twentieth century. The method The basis of our research is the historical-cultural, comparative-typological and figurative-stylistic research methods, which made it possible to achieve a holistic analysis of the graphic works of V. Efimenko. The main thing is the art history analysis of works of book and easel graphic. The last third of the twentieth century is marked by changes in the cultural life of the country. Ukrainian artists sought to join the European and world trends in artistic development, which was characterized by a variety of styles and methods. Despite the fact that state requirements and standards were of great importance, the artists tried to put in to practice the socially relevant topics of concern to them. Two directions of the master's creativity are considered: book and easel illustration. The relationship between the individual graphic style of V. Efimenko and the general artistic process is considered. On the basis of the artistic and stylistic analysis, the interrelation of V. Efimenko’s creativity with the Ukrainian and world artist revealed. It is revealed that the master's works are characterized by a deeply personal, philosophical reading of texts and their figurative reproduction in the language of graphics. It is noted that V. Efimenko could express his philosophical ideas thanks to his free possession of linocut and etching techniques.